MULTIPURPOSE FERTILIZER SPREADING MACHINE: DESIGN AND FABRICATION - Sushant Jadhav; Akash Mane; Sandip Bagul; Omkar Jagtap; Rambhajee Nagargoje; Digambar Kashid; Pradeep Pawar (International Journal of Innovations in Engineering Research and Technology, 2022)
The paper provides information on the different types of new developments in manure dispenser which are available these days. Fertilizer spreading machine is an important tool in the agriculture part. The modern era is marching towards rapid growth in all sectors including the agricultural sector. Meet the next meal Demands, farmers must adopt new strategies that will not interfere soil texture however will increase overall crop production. This paper is interactive with various throwing of the fertilizer methods used in India to distribute the fertilizer machine. Comparison between traditional dumping of the fertilizer method and proposed new machine, which can make a price simultaneous operation and has a number of benefits. Fertilization of land is one of the important and common procedure before the cropping of seeds this work is carried out mostly by the machineries and labours which will include the cost for fertilization process for big and large farms it also become costly and time required to do also more. The main objective of our multipurpose fertilizers spreading machine is to reduce time and cost for fertilizers process by reducing the human efforts. Along with Fertilizers we can spread seeds as well. As daily activity availability becomes a major concern for farmers and labour costs are higher, this machine reduces the total effort and cost of composting the throwing of throwing fertilizer and manure. In this work, we are discussed about multipurpose fertilizer spreading machine.